2014
DOI: 10.1073/pnas.1319569111
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4-mediated mechanotransduction regulates the metabolic response of chondrocytes to dynamic loading

Abstract: Mechanical loading of joints plays a critical role in maintaining the health and function of articular cartilage. The mechanism(s) of chondrocyte mechanotransduction are not fully understood, but could provide important insights into new physical or pharmacologic therapies for joint diseases. Transient receptor potential vanilloid 4 (TRPV4), a Ca 2+ -permeable osmomechano-TRP channel, is highly expressed in articular chondrocytes, and loss of TRPV4 function is associated with joint arthropathy and osteoarthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
470
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 384 publications
(503 citation statements)
references
References 58 publications
27
470
5
1
Order By: Relevance
“…Our discovery provides, to our knowledge, the first direct evidence that mechanically sensitive ion channels in articular chondrocytes are necessary for these cells' response to high-strain mechanical cues. These findings complement recent results from our group reporting that the anabolic response of chondrocytes to low-level, physiologic mechanical loading, is regulated by a TRPV4-based mechanism (20). In addition, we have previously reported that loss of TRPV4 leads to age-dependent osteoarthritis in mice (19).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our discovery provides, to our knowledge, the first direct evidence that mechanically sensitive ion channels in articular chondrocytes are necessary for these cells' response to high-strain mechanical cues. These findings complement recent results from our group reporting that the anabolic response of chondrocytes to low-level, physiologic mechanical loading, is regulated by a TRPV4-based mechanism (20). In addition, we have previously reported that loss of TRPV4 leads to age-dependent osteoarthritis in mice (19).…”
Section: Discussionsupporting
confidence: 91%
“…Although many different mechanisms have been shown to be involved in chondrocyte mechanotransduction (13,(15)(16)(17), recent studies show that the cation channel, TRPV4, is responsible for mediating the anabolic response of chondrocytes to osmotic or mechanical stress (18)(19)(20). In this regard, identification of the mechanosensitive pathways involved in cartilage homeostasis as well as injury will help to provide novel targets for rational treatment of cartilage injury and posttraumatic osteoarthritis (21).…”
mentioning
confidence: 99%
“…While previous studies have found the importance of volume regulation by chondrocytes in cartilage physiology 4244 , our work demonstrates that chondrocytes utilize changes in volume to sense the viscoelastic properties of their microenvironment. In adherent cells, it is known that cells sense viscoelasticity through exerting traction forces at integrin-ECM ligand adhesions, gauging resistance to traction forces, and clustering ligands 18,4548 .…”
Section: Discussioncontrasting
confidence: 47%
“…Biomechanical signals are also multiscale responding to age and disease, Figure 3, with effects at a tissue level (differential loading across joint, load sharing across particular tissues), within a tissue (differential compression on zonal regions of cartilage) and cell‐associated (mechanotransduction through the pericellular matrix of the chondron) 61. Critically, there is not a single mechanical signal that transduces into an electrical or chemical signal intracellularly and different forces require a level of integration (compression, osmolarity, fluid shear, hydrostatic pressures); the contribution of each still needs to be defined 73. Given that mechanical signals have to be transduced through the extra‐ and peri‐cellular matrix to allow chondrocytes to respond to their physical environment mechanotransduction mechanisms are potential therapeutic targets.…”
Section: Biology As a Systemmentioning
confidence: 99%
“…Using a mechanistic approach a Ca 2+ responsive osmomechano‐TRP channel TRPV4 was found to be critical to transduction of mechanical and osmotic signals76 with enhanced anabolic gene expression and increased matrix production demonstrated using a chemical agonist 73. Further work, using a cartilage‐specific, inducible knock‐out of Trpv4 revealed a reduction in age‐associated OA at 12 months, but not in a DMM model 77.…”
Section: Biology As a Systemmentioning
confidence: 99%